Perbedaan Pengetahuan Dan Sikap Siswa Tentang Pencegahan Penyakit Typoid Dengan Metode Bola Salju Dan Ceramah Pada Siswa SD Di Kecamatan Nogosari Kabupaten Boyolali - Aliman, Aliman; , Heru Subaris Kasjono, S.K.M., M.Kes; , Farid Setyo Nugroho, S.K.M (2015)
Typhoid fever is caused by sallmonella typhosa, which transmits its infection through water contaminated by feces and urine of typhoid patients. Nogosari Sub-districtis endemic in typhoid so the disease reappears at any time. Early prevention is necessary through elementary school students by improving their knowledge and attitudes. This study aims to determine the impact of health education about typhoid fever preventiontowards levels of knowledge and attitudes of students at SD Negeri III Nogosari and SD Negeri I Keyongan Nogosari Boyolaliusing snowball and lecturing methods. Researchers use Quasi-Experimental method withpre-test post-test design. The subjects of this study are elementary students from fourth to fifth grade from two elementary schools that are divided into two groups. The two groups, Snowball group from SD Negeri III Nogosari and Lecturing group from SD Negeri I Keyongan, have 80 samples in total. Statistical test with the significance level(α=0,05) uses paired sample t-test, showing that there are differences in the average value of knowledge (p-value=0,000) and attitudes (p-value=0,000) in lecturing group. Statistical result of the independent t-test shows that there are differences in snowball and lecturing methods about typhoid fever prevention towards knowledge (p-value=0,011) and attitudes (p-value=0,000). Keywords: Lecturing, knowledge, and attitudes.